Tailoring the Magnetic Properties of Fe Asymmetric Nanodots - Altbir-Drullinsky, D; Escrig-Murua, J; Vargas-Ayala, N (2011)
Asymmetric dots as a function of their geometry have been investigated using three-dimensional (3D) object oriented micromagnetic framework (OOMMF) code. The effect of shape asymmetry of the disk on coercivity and remanence is studied. Angular dependence of the remanence and coercivity is also addressed. Asymmetric dots are found to reverse their magnetization by nucleation and propagation of a vortex, when the field is applied parallel to the direction of asymmetry. However, complex reversal modes appear when the angle at which the external field is applied is varied, leading to a non-monotonic behavior of the coercivity and remanence. © 2011 Elsevier B.V. All rights reserved.